Optimal policy rules at home, crisis and quantitative easing abroad - Paul D. McNelis (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
This paper examines the international transmission of financial shocks which originate in, and are partially offset by, quantitative easing in a large financially-stressed country. Using a two-country model, we evaluate the adjustment in the non-stressed home country, following recurring negative shocks to productivity and banking-sector balance-sheet/terminal wealth ratios. We first examine the application of QE policies in the stressed foreign country. Coupling quantitative easing with crisis events abroad magnifies the financial instability transmitted to the rest of the world. Our results show that the non-stressed home country can make effective use of tax-rate rules for consumption, or taxes to stabilize financial-sector net worth in times of prolonged crisis abroad.
URN:NBN:fi:bof-201610311470
Keywords: E44; E58; F38; F41; 330